Heat Transfer Design, Experimentation and Applications - Araiz Vega, Miguel (IntechOpen, 2021)
Thermal energy is present in all aspects of our lives, including when cooking, driving, or turning on the heat or air conditioning. Sometimes this thermal management is not evident, but it is essential for our comfort and lifestyle. In addition, heat transfer is vital in many industrial processes. Thermal energy analysis is a complex task that usually requires different approaches. With five sections, this book provides information on heat transfer problems and using experimental techniques and computational models to analyse them.